Physico-chemical characterization of essential oil from the peel and leaf of Dalanghita (Citrus nobilis) - Agapin, Julienne Stephanie Fabie (Miag-ao, Iloilo University of Philippines Visayas, 2015)
Citrus rank as the fourth most important type of fruit produced in the Philippines after banana, mango and pineapple. Citrus nobilis, which is grown primarily in Guimaras and the Panay Island, is sold mainly for its juice and pulp while the peels and the leaves are left to waste. In order to maximize the value of the plant, essential oils will be extracted from both the peels and leaves of C. nobilis via steam distillation. Physicochemical analysis of the dalanghita peel (PEO) and leaf (LEO) essential oils will determine their potential application in the industry. Investigation of their physical properties showed that the density, color, odor, congealing identified seven compounds in the PEO, and twelve compounds in the LEO. D-Limonene, gamma-Terpinene, beta-Linalool, and diethyl phthalate were identified to be present in both essential oils. Antioxidant property of the oils were tested using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay with the LEO showing an IC50 = 150ppm while the PEO has an IC50 = 493 ppm. Antibacterial properties of the oils were tested using the Kirby Bauer Disc Diffusion method both oils showed activity against E. coli and S. aureus.
Special Problem (Master of Chemistry) -- Miagao, Iloilo :University of the Philippines Visayas, September 21,2015.